Small claims procedure for consumer relations - law n°18.507 do its procedural aspects result in a beneficial tool for the consumer? - Sorribas Musi, Stefanía L. (2022)
In the present investigation, an analysis of Law No. 18,507 “Consumer defense”, considering the same together with Law No. 17,250 “Consumer relations law" and the General Process Code. In the course of this study, the various procedural aspects of said Law will be considered in particular, in order to reach a conclusion to answer the question that is the object of this work. The study of jurisprudence and the comparison of statistics of claims processed in administrative channels and procedures initiated in judicial channels under the protection of said regulations, complement the foundations on which I base myself to answer this question. Also, the work includes an analysis at the regional level, which allows us to observe the good position in which our country is located.